Variable and constraint reduction techniques for the temporal bin packing problem with fire-ups - Martinovic, John (2022)
The instances were solved by the commercial software Gurobi. The underlying implementation of the models in Python can be found in https://github.com/wotzlaff/tbpp-cf2.